International economics : understanding the forces of globalization for managers - Torelli, Paul. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2013)
Today's news media displays an intense fascination with the global economy--and for good reason. The degree of worldwide economic integration is unprecedented, and rising globalization has lifted living standards and reduced poverty. Foreign markets and new technologies continue to present opportunities for entrepreneurs and corporations. Still, economic shocks can spread across the world in minutes, impacting billions of lives. Citizens are understandably anxious in this age of macroeconomic turbulence and overextended governments. Modern economics offers a powerful framework for understanding globalization, international trade, and economic growth. Many managers possess years of hands-on experience dealing with business cycles and foreign competitive pressures, yet these leaders may not have a solid grounding in economic concepts that shed light on the forces of globalization. This book explains economics in everyday language, using little or no math, giving businesspersons better tools to interpret current events as well as long-term economic and political developments.
1. A brief history of modern economic globalization -- 2. Economic growth, convergence, and trade -- 3. Theories of international trade -- 4. Industrialization, globalization, and labor markets -- 5. Politics, globalization, and the state -- 6. Poverty, progress, and critics of globalization -- Epilogue -- Index.
Part of: 2013 digital library.
Includes bibliographical references and index.
Title from PDF title page (viewed on September 27, 2013).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: International economic relations; Globalization; economics; human capital; financial crisis; macroeconomics; comparative advantage; absolute advantage; emerging economy; international trade; business strategy; economic growth; economic history; international economics; political economy; economic development; industrialization; labor market; convergence; New World; mercantilism; Industrial Revolution; productivity; technology; capital control; intellectual property; research and development; productivity slowdown; Adam Smith; factor proportions model; gravity model; infant industry; import substitution; Asian Tiger; trade policy; tariff; public choice; rent seeking; trade agreement; free trade; liberalization; information and communications technology; vertical integration; supply chain; poverty trap; big push; coordination failure; industrial policy; diversification; value added; managerial capital; skill biased technological change; population growth; wage inequality; middle income trap; tradable sector; offshoring; outsourcing; foreign direct investment; skill upgrading